Fabrication and appraisal of targeted axitinib loaded bilosomes for the enhanced breast and ovarian anticancer activity - Randa Mohammed Zaki; Basmah Nasser Aldosari; Layla A. Alkharashi; Alyaa Alsalhi; Fatma I. Abo El-Ela; Raneem Meshal Alosaimi; Maha Alsunbul; Obaid Afzal; Mayada Said (PLoS ONE, 2025)
The goal of this study was the formulation and optimization by statistical means of bilosomal formulations of axitinib (AXT) in order to improve its anticancer efficacy in a targeted manner. A central composite rotatable design was employed Using Design-Expert® software. The formulation factors were cholesterol, span 60, and sodium deoxy cholate (SDC) amounts (mg), whereas the dependent responses were Entrapment efficiency (EE%), Vesicles’ size (VS), and Zeta potential (ZP). The design expert software was utilized to perform the numerical optimization process. The optimized bilosomal formulation was assessed using differential scanning calorimetry (DSC), X-ray diffraction (XRD), transmission electron microscope (TEM), in-vitro release study, short-term stability study, and in-vitro cell proliferation assay and flow cytometry on MCF-7 breast and OV-2774 ovarian cancer cell lines. The optimized formulation was found to be composed of 19.999, 111.869 and 15 mgs of cholesterol, span 60, and SDC, respectively with a desirability of 0.753. EE%, VS, and ZP were predicted to be 88.4977%, 594.592 nm, and −44.2354 mV, respectively. The validation process on the optimized formula demonstrated that the variation from the predicted responses was less than 5%. The DSC and XRD studies revealed that AXT was entrapped within the bilosomal vesicles. The optimized AXT bilosomal formulation exhibited spherical non-aggregated nanovesicles in TEM images. Furthermore, it improved AXT release when compared to AXT suspension. According to stability experiments, the optimum bilosomal formulation was stable for thirty days. The cytotoxicity of the optimized bilosomal formulation was enhanced on the MCF-7 breast and OV-2774 ovarian cancer cell lines compared to AXT suspension even at lower concentrations. Flow cytometry showed that AXT loaded BSMs made a significant increase in the percentage of apoptotic cells in MCF-7 and OV-2774 cells, respectively. Molecular docking suggests that axitinib and SDC decreased the activation of the caspase-8 receptor on the surface of ovarian and breast cancer, which consequently led to an increase in anticancer activity. So, BSMs might be regarded a promising carrier of AXT to target ant treat breast and ovarian cancers.